Communalism: narratives in Chhattisgarh - Saumya (2008)
The expansion of the Vanvasi Kalyan Ashram's activities amongst tribals in Chhattisgarh shows the influence of communalism in these areas. The strategies used by the organisation along with other Hindutva outfits in Jashpur, for example, delineate how communalism works to crystallise religious identities by playing upon the socio-political and cultural background there. - Reproduced.
Keywords: Communalism - India - Chhattisgarh; Communalism